Exploratory factor analysis of the Indonesian version of MMPI-2-RF Restructured Clinical (RC) Scales - Widhi Adhiatma; Magdalena S. Halim (Universitas Ahmad Dahlan, 2019)
The Minnesota Multiphasic Personality Inventory (MMPI) is the world’s most frequently used scale, both in clinical assessment and psychiatric setting. This measure has been revised several times with MMPI-2-RF (Restructured Form) being the latest version. The Restructured Clinical (RC) Scales, which contains nine sub-scales, is the primary clinical scale in MMPI-2-RF. This scale replaces the Clinical Scales from the previous version of MMPI. This research aimed to analyze the construct validity of the RC Scales using Exploratory Factor Analysis (EFA) technique. The sample of this research involved 279 participants (male = 26.5%; female = 73.5%) with an average of 21.63 years old. The obtained data was analyzed using EFA through Principal Component Analysis (PCA). Results showed that Restructured Clinical Scales consisted of one factor solution, namely psychological disorder. The number of the factors, as well as the structure, was different from the US version of MMPI-2-RF Restructured Clinical Scales. Through these findings, MMPI-2-RF users in Indonesia are expected to be more cautious when interpreting the Restructured Clinical Scales sub-scales score.